EU lay communication in translation: mediation, affectivity and EU citizenship: A contrastive multilingual critical discourse analytic approach to translation. (3rd March 2020) - Constantinou, Maria
ABSTRACT: Translation within European Union (EU) institutions has attracted the attention of scholars in Translation Studies who have mainly investigated legal documents and focussed on their hybridity, ideological significance, quality or their normative function. This study deals with an under-researched genre, that of EU lay communication. In particular, it examines some versions of a recent EU promotional material: 60 Gründe für die EU'. Warum wir die EU nach wie vor brauchen, initially drafted in German and then rendered in the linguacultures of the EU. Capitalizing on Systemic Functional Linguistics and appraisal theory, it focusses on two versions for Greece and for Cyprus, alongside other translations of the same document (for Ireland, Malta, France, and Germany). It investigates the translators' intervention, and how ideological shifts are likely to distort the meaning potential from the viewpoint of the ideational and interpersonal metafunctions of the texts studied, which seem to affect the EU's agency and affective citizenship. It concludes that the version for Greece is often maximally mediated, introducing shifts that do not serve the purpose of the initial text, while the version for Cyprus, like the other versions under attention, contributes to a more positive evaluation of the institutions.